Увеличение добротности плазмонных резонансов в цепочке металлических нанопроводов - Стогний, Н. П.; Сахненко, Н. К. (ХНУРЭ, 2012)
Plasmon resonances and their quality factors of an isolated metal wire and of a linear chain of coupled metal wires are theoretically investigated. Mechanism of the plasmonic modes coupling that can be considered as symmetric and antisymmetric combinations of isolated wire plasmons is investigated. Accurate analysis of the spectrum of different plasmon resonances is presented. Significant enhancement of the plasmonic quality factor is revealed.
Keywords: Нанопровод; добротность